Ixekizumab for the treatment of patients with active psoriatic arthritis and an inadequate response to tumour necrosis factor inhibitors: results from the 24-week randomised, double-blind, placebo-controlled period of the SPIRIT-P2 phase 3 trial. Issue 10086 (10th June 2017) - Nash, Peter; Kirkham, Bruce; Okada, Masato; Rahman, Proton; Combe, Benard; Burmester, Gerd-Ruediger; Adams, David H; Kerr, Lisa; Lee, Chin; Shuler, Catherine L; Genovese, Mark; ,
Summary: Background: Patients who have had inadequate response to tumour necrosis factor inhibitors have fewer treatment options and are generally more treatment refractory to subsequent therapeutic interventions than previously untreated patients. We report the efficacy and safety of ixekizumab, a monoclonal antibody that selectively targets interleukin-17A, in patients with active psoriatic arthritis and previous inadequate response to tumour necrosis factor inhibitors. Methods: In this double-blind, multicentre, randomised, placebo-controlled, phase 3 study (SPIRIT-P2), patients were recruited from 109 centres across ten countries in Asia, Australia, Europe, and North America. Patients were aged 18 years or older, had a confirmed diagnosis of psoriatic arthritis for at least 6 months, and had a previous inadequate response, distinguished by being refractory to therapy or had loss of efficacy, or were intolerant to tumour necrosis factor inhibitors. Patients were randomly assigned (1:1:1) by a computer-generated random sequence to receive a subcutaneous injection of 80 mg ixekizumab every 4 weeks or every 2 weeks after a 160 mg starting dose or placebo. The primary endpoint was the proportion of patients who attained at least 20% improvement in the American College of Rheumatology response criteria (ACR-20) at week 24. This study is registered withClinicalTrials.gov, numberNCT02349295 . Findings: Between March 3, 2015, to March 22, 2016, 363 patients were randomly assigned to placebo (n=118), ixekizumab every 4 weeks (n=122), or ixekizumab every 2 weeks (n=123). At week 24, a higher proportion of patients attained ACR-20 with ixekizumab every 4 weeks (65 [53%] patients; effect size vs placebo 33·8% [95% CI 22·4–45·2]; p<0·0001) and ixekizumab every 2 weeks (59 [48%] patients; 28.5% [17·1–39.8]; p<0·0001) than did patients with placebo (23 [20%] patients). Up to week 24, serious adverse events were reported in three (3%) patients with ixekizumab every 4 weeks, eight (7%) with ixekizumab every 2 weeks, and four (3%) with placebo; no deaths were reported. Infections were reported in 47 (39%) patients with ixekizumab every 4 weeks, 47 (38%) with ixekizumab every 2 weeks, and 35 (30%) with placebo. Three (2%) serious infections, all in patients in the ixekizumab every 2 weeks group, were reported. Interpretation: Both the 2-week and 4-week ixekizumab dosing regimens improved the signs and symptoms of patients with active psoriatic arthritis and who had previously inadequate response to tumour necrosis factor inhibitors, with a safety profile consistent with previous studies investigating ixekizumab. Funding: Eli Lilly and Company.